Measurement of Oil Slick Transport and Evolution in the Gulf of Mexico using L-band Synthetic Aperture Radar - Jones, Cathleen; Espeseth, Martine; Holt, Benjamin; Brekke, Camilla (VDE Verlag, 2018)
Source at https://www.vde-verlag.de/proceedings-en/454636104.html The transport and evolution of a mineral oil slick originating at a seep in the Gulf of Mexico approximately 16 km offshore of the mouth of the Mississippi River is measured using a series of images acquired at 40 minute intervals with the Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR), an L-band, high resolution, high signal-to-noise instrument operated by the U.S. National Aeronautics and Space Agency (NASA). A series of four images acquired over a 2-hour time period is used in the study. Both VV-intensity images and the VVintensity contrast between the slick and clean water (damping ratio) are used. The intensity images show the spatial development and transport of the slick within an area extending from the source northward to near the Louisiana (USA) coast. The slick initially spreads to the northeast from the origin site, then become entrained in an along-shore current. From there, the direction of transport changes by nearly 180º, and the oil from the slick moves west along a path much closer to the Louisiana shoreline. Concentration of the oil within the slick is observed along fronts and internal waves. The oil that remains on the surface the longest shows increasing damping, which could indicate the formation of more stable emulsions that can persist in the environment.